GAMBARAN MINDFULNESS PADA PENGGUNA NARKOBA SUNTIK YANG MENJALANI PROGRAM TERAPI RUMATAN METADON - Eric Sindunata; Elmira N. Sumintardja (MANASA, 2016)
This research aims to describe the level of mindfulness on IDU that enroll in PTRM. The description is needed because there is an increase rate of drug use in Indonesia. The drug use inflicts adverse effect on the user, especially for injected drug users. IDU experience severe problem in their Quality of Life, Psychological Well Being, depression, and anxiety. Other concern about IDU is the high risk of trasmitted disease. Based on the condition, the government organizes the PTRM. However, it is found that there is such a lack of discipline among the participants. The lack discipline is the result of the lack of knowledge about PTRM, that make a lot of the participants tend to mix the metadon with other medicine or relapse in his/her drug use. The lack of knowledge usually due to the lack of openness of the participants. The openness is related to mindfulness. Effort to increase mindfulness is assumed would have effect on the effectiveness of PTRM. The study was conducted with a quantitative approach with some additional data from interview and observation. The measurement implemented was FFMQ, which consists of 39 items that divided into five indicators: observe, describe, actaware, nonjudge, and nonreact. The participants were 124 people that attend PTRM in Jakarta health center that include in the reaching program of Kios Atma Jaya. The result showed that the participants of PTRM that still mix their metadon had a lower score of mindfulness in observe, nonjudge, nonreact, and total score. It was very different if we compare the score with the score of participants that never mix their metadon anymore, their average score was belong to moderate category.